Legal Analysis of Financial Sector Supervision and Regulation for Consumer Protection in Financial Services - Guntara, Deny; Abas, Muhamad (UNISSULA, 2025)
The establishment of the Financial Services Authority (Otoritas Jasa Keuangan/OJK) is rooted in a critical evaluation of banking supervision in Indonesia. The issuance of Government Regulation No. 4 of 2023 concerning the Strengthening and Development of the Financial Sector is an effort by public institutions to encourage government support through changes in Indonesia’s monetary sector. This study examines how Law No. 4 of 2023 impacts financial services actors (market conduct), its effect on the consumer protection system in financial services, and its influence on financial education and literacy in society. This study uses a normative legal research method with a juridical-normative approach. Government Regulation No. 4 of 2023 has a positive impact by strengthening the authority of the OJK to supervise the behavior of the financial industry. This aims to protect consumers’ interests, maintain national economic stability, and provide legal certainty for businesses in the financial technology sector. The Financial Technology Industry Law has a positive impact on financial sector consumers. This law not only protects consumers and regulates the financial technology industry but also emphasizes the importance of financial literacy education. The Government Regulation No. 4 of 2023 acts like a pseudo-down payment provision within supported monetary policies and provides security for buyers in the monetary sector. This study concludes that Government Regulation No. 4 of 2023 significantly strengthens the legal framework for regulating market conduct and protecting financial consumers in Indonesia.